Increasing Interest and Learning Outcomes in Mathematics Using the Problem Based Learning Method in Class II of SDN 016 Sungai Pinang Samarinda: Peningkatan Minat Dan Hasil Belajar Matematika Menggunakan Metode Problem Based Learning Pada Kelas II SDN 016 Sungai Pinang Samarinda - Nur Agus Salim; Rizqi Syafrina; Alfionita Damayanti (Borneo Educational Journal (Borju), 2021)
This research aims to increase student interest and learning outcomes in Mathematics subjects through the Problem Based Learning learning method in class II. SDN 016 Sungai Kunjang Samarinda 2017/2018 Academic Year. The method used in this research is Classroom Action Research (PTK), which is carried out in 3 cycles, with three meetings in each cycle. The research subjects were 38 class II students consisting of 19 men and 19 women in the second semester of the 2017/2018 academic year. From the results of the questionnaire, student interest in learning before carrying out the research was 33.80%. It increased at the end of the research implementation by 54.36%. In comparison, the average results of student observations in cycle I was 10.95%, cycle II was 15.68%, and increased in cycle III by 21.18%, for the average student learning outcomes in pre-cycle was 62.79, cycle I was 68.42, cycle II was 73.64 and increased in cycle III was 78.97 with learning completeness is 100%. Based on the above analysis of the results of research conducted at SDN 016 Sungai Pinang Samarinda, the Problem-Based Learning Method can increase interest and learning outcomes in Mathematics for class II students.